Morbidity associated with amphetamine-related presentations to an emergency department: A record linkage study - Fatovich, D.; Davis, G.; Bartu, Anne (Blackwell Publishing, 2012)
Objective: Amphetamine use is a global public health problem. We examined hospitalisations in a cohort of 138 patients who presented with an amphetamine-related problem to an ED in2005. Methods: A record linkage study, using the morbidity, ED and mortality databases in the Data Linkage Unit of the Department of Health, Western Australia. The main outcome measures were hospital separations and length of stay (LOS) 5 years before and 4 years after entry into the cohort. Results: One hundred and thirty patients (94%) with an amphetamine-related presentation had a link with the hospital morbidity dataset. The most common diagnosis before and after cohort entry was mental disorders (before: F00-F99; 405 separations, total LOS 2570 days; after: 309 separations, total LOS 3671 days). Injury and poisoning was the next most common in both time periods. Men had an increased relative risk (RR) for all days of psychiatric care (RR 2.12, 95% CI 1.04–4.35). After adjusting for age and sex, the highest risks of increased LOS occurred within 1 year before (RR 2.22, 95% CI 1.01–4.91) and 2 years post entry into the cohort (RR 4.21, 95% CI 1.87–9.46 and RR 2.82, 95% CI 1.25–6.34). There were four (2.9%, 95% CI 0.9–7.7%) deaths, which occurred within 2 years post cohort entry. Conclusion: Amphetamine-related presentations to the ED are associated with a significant cluster of hospitalisations around that episode. This is most prominent for psychiatric diagnoses, with a large increase in the total LOS in the year following cohort entry. Counselling less risky behaviour might decrease the burden of illness.